(untitled) (The Review of Diabetic Studies, 2025)
Background: Dental science has evolved into a technology-driven discipline that integrates digital systems, advanced biomaterials, and artificial intelligence. These innovations have transformed diagnostics, treatment planning, and patient care, shifting the field toward precision and personalized dentistry. This review highlights emerging trends and technologies shaping modern dental practice. Methods: A comprehensive narrative review was conducted using data from PubMed, Scopus, and Web of Science (2015–2025). Peer-reviewed articles, clinical studies, and systematic reviews focusing on dental materials, digital technologies, imaging, regenerative approaches, and implantology were analyzed. Thematic synthesis emphasized innovation, translational potential, and clinical relevance. Results: Recent advances include bioactive restorative materials, nanostructured ceramics, and regenerative scaffolds that promote tissue healing. Digital dentistry, CAD/CAM systems, and 3D printing have improved precision, efficiency, and customization. Artificial intelligence enhances diagnostic accuracy in caries detection, periodontal analysis, and treatment planning, while novel imaging modalities such as optical coherence tomography and hyperspectral imaging enable non-invasive visualization. In periodontics and implantology, regenerative and patient-centered approaches are improving outcomes and linking oral with systemic health. Conclusions: Dental science is entering a new era defined by digital integration, biological regeneration, and personalized care. Continued interdisciplinary research and ethical implementation are essential to ensure that technological innovations translate into equitable, sustainable, and high-quality oral healthcare worldwide.